1983
DOI: 10.1056/nejm198301273080402
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric-Oxygen Treatment of Multiple Sclerosis

Abstract: Several uncontrolled studies have suggested a beneficial effect of hyperbaric oxygen on multiple sclerosis. We studied 40 patients with advanced chronic multiple sclerosis who were randomly divided into two matching groups. The experimental group received pure oxygen, and the placebo group received a mixture of 10 per cent oxygen and 90 per cent nitrogen; both groups were treated at a pressure of 2 atmospheres absolute for 90 minutes once daily, for a total of 20 exposures. Objective improvement occurred in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Such an acute effect would not have been detected by the protocols used in the clinical trials of the contentious hyperbaric oxygen (HBO) therapy 30 years ago. 52,53 Whereas some patients today remain confident that HBO improves symptoms such as fatigue and bladder control, most neurologists remain skeptical of beneficial effects based on the findings of the clinical trials. The trials were founded in a belief that oxygen may alter the course of the disease, and so they were typically designed to detect a change in motor ability assessed up to 1 year after a bout of HBO exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Such an acute effect would not have been detected by the protocols used in the clinical trials of the contentious hyperbaric oxygen (HBO) therapy 30 years ago. 52,53 Whereas some patients today remain confident that HBO improves symptoms such as fatigue and bladder control, most neurologists remain skeptical of beneficial effects based on the findings of the clinical trials. The trials were founded in a belief that oxygen may alter the course of the disease, and so they were typically designed to detect a change in motor ability assessed up to 1 year after a bout of HBO exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs such as histamine and amyl nitrite, which increase perfusion and thus may counteract energy failure, provided only temporary beneficial effects [ 129 ]. Similarly, hyperbaric oxygen has highly significant transient effects in the treatment of patients with multiple sclerosis but failed to show any lasting results (e.g., 100% oxygen at 2 atmospheres for 90 min once daily, for a total of 20 exposures) [ 130 , 131 ]. The failure of hyperbaric oxygen therapy in patients with multiple sclerosis may be related to oxidative stress, which can increase in such conditions, similar to reperfusion injury [ 132 ] and the temporal timing of oxygen delivery in oxygen-sensitive periods [ 113 ].…”
Section: Clinical Consequencesmentioning
confidence: 99%
“…Apparently, this society had great difficulty accepting the results of the work Dr. Fischer had completed, and multiple revisions were made to weaken the conclusions sufficiently to satisfy the editors of the New England Journal of Medicine. In this double-blind controlled study of patients with advanced chronic disabilities, Fischer found significant improvement in objective measurements, and the treatment effect persisted for at least 1 year [ 7 ].…”
Section: Introductionmentioning
confidence: 99%